Carbon, nitrogen and stable carbon isotopes in the sediment core C49 from Central Segara Anakan, Indonesia - Mariska Astrid Kusumaningtyas; Andreas A Hutahaean; Tim C Jennerjahn (PANGAEA, 2018)
What was sampled: Mangrove sediment Parameter measured and method: 1. Organic carbon (Corg), analyzed using elemental analyzer (Eurovector E3000 Elemental Analyzer) 2. Total nitrogen (N), analyzed using elemental analyzer (Eurovector E3000 Elemental Analyzer) 3. Stable carbon isotope composition (δ13Corg), analyzed using Thermo Finnigan Delta plus mass spectrometer coupled to a Flash EA1112 Elemental Analyzer Where was sampled: Central Segara Anakan Lagoon, Central Java, Indonesia When was sampled: Sediment samples were taken in November 2016. How it was sampled: Mangrove sediments were collected using a 1 m long semi-cylindrical auger. Sediments were taken down to 1 m depth, and were sampled in 5 cm interval.
In supplement to: Kusumaningtyas, Mariska Astrid; Hutahaean, Andreas A; Fischer, Helmut W; Pérez-Mayo, Manuel; Ransby, Daniela; Jennerjahn, Tim C (2019): Variability in the organic carbon stocks, sources, and accumulation rates of Indonesian mangrove ecosystems. Estuarine, Coastal and Shelf Science, 218, 310-323, https://doi.org/10.1016/j.ecss.2018.12.007